KONSISTENSI DAN EFEKTIVITAS PERAN LEMBAGA KEUANGAN NON BANK (KOPERASI SIMPAN PINJAM) SEBAGAI PENGGERAK PEREKONOMIAN INDONESIA - Ompusunggu, Dicky Perwira; Sutrisno, Depy Rizkika Indria; Hukom, Alexandra (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
A savings and loan cooperative, also called a credit cooperative, is a cooperative that allocates the deposits of its members who need capital support for their business. The purpose of this paper is to provide information about Savings and Loan Cooperatives that have the potential to contribute to the Indonesian national economy. With the continued development of Savings and Loans Cooperatives throughout Indonesia, it is hoped that it can help MSME business actors who are members of the Savings and Loans Cooperative to develop their businesses so that they can create jobs and reduce poverty in Indonesia. In this study, a literature study method was used that aims to understand the role of non-bank financial institutions, namely savings and loan cooperatives, to find out how savings and loan cooperatives are a driving factor for the economy in Indonesia.This research also uses descriptive analysis based on literature reviews of journals, articles, books and other research. With the results of research that savings and loans cooperatives play an important role in the economic development of the people in Indonesia. The main purpose of establishing cooperatives, which are one of the driving forces of the national economy, is to protect the welfare of rural communities and has expanded its establishment to the present.